Transcriptomic and Physiological Evidence for the Relationship between Unsaturated Fatty Acid and Salt Stress in Peanut - Sui, Na; Wang, Yu; Liu, Shanshan; Yang, Zhen; Wang, Fang; Wan, Shubo (Frontiers in Plant Science, 2018)
Peanut (Arachis hypogaea L.) is one of the five major oilseed crops cultivated worldwide. Salt stress is a common adverse condition for the growth of this crop in many countries and regions. In this study, physiological parameters and transcriptome profiles of peanut seedlings exposed to salt stress (250 mM NaCl for four days, S4) and recovery for 3 days (when transferred to standard conditions for 3 days, R3) were analyzed to detect genes associated with salt stress and recovery in peanut. We observed that the quantum yield of PSII electron transport (ΦPSII) and the maximal photochemical efficiency of PSII (Fv/Fm) decreased in S4 compared with the control, and increased in R3 compared with those in S4. Seedling fresh weight, dry weight and PSI oxidoreductive activity (∆I/Io) were inhibited in S4 and did not recover in R3. Superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities decreased in S4 and increased in R3, whereas superoxide anion (O2−•) and hydrogen peroxide (H2O2) contents increased in S4 and decreased in R3. Transcriptome analysis revealed 1742 differentially expressed genes (DEGs) under salt stress and 390 DEGs under recovery. Among these DEGs, two DEGs encoding ω-3 fatty acid desaturase that synthesized linolenic acid (18:3) from linoleic acid (18:2) were down-regulated in S4 and up-regulated in R3. Furthermore, ω-3 fatty acid desaturase activity decreased under salt stress and increased under recovery. Consistent with this result, 18:3 content decreased under salt stress and increased under recovery compared with that under salt treatment. In conclusion, salt stress markedly changed the activity of ω-3 fatty acid desaturase and fatty acid composition. The findings provide novel insights for the improvement of salt tolerance in peanut.